LA EVALUACIÓN INVESTIGATIVA EN CIENCIAS A NIVEL UNIVERSITARIO - Alfredo Moncayo, Guido; María Cabrera, Francia (Tecné, Episteme y Didaxis: TED, 1998)
The evaluation plays different roles in the educational process. It should be considered as a learning process and not as a result of learning. ln this paper we develop the strategy of evaluation as a research process, in which the student has the opportunity to summarize to solve problems , to read papers to integrate knowledge to develop competence in which he must apply the knowledge and socialize his own research.